Purchase of prescription and OTC medicines in Slovakia: factors influencing patients' expectations and satisfaction (Brazilian Journal of Pharmaceutical Sciences, 2017)
Slovakia is a country where the purchase of OTC (over the counter) medicines outside the pharmacy is not allowed by the government. This study aimed at evaluating patients' satisfaction and acceptance of community pharmacists. Customer's behaviour and expectations influencing the purchase of prescription and OTC medicines were analyzed. A structured questionnaire having 15 multiple-choice questions was used to analyze the descriptive parameters. Data collection lasted from January to February 2014. The sample size consisted of 357 high-school educated individuals under 40 years of age. The survey showed that the prescription and OTC medicines were bought equally. The participants reported a 96.0%, 96.3% and 90.2% satisfaction rate with willingness and approach of the community pharmacist, pharmacy services and provision of drug information respectively. As for the OTC medicines, 89.5% people considered the pharmacist an expert: 88.2% purchased medicines with pharmacist's recommendation, 97.8% needed a professional counselling and 97.2% required a pharmacist's guidance. As for the prescription drugs, only 72.1% considered the pharmacist an expert: 96.3% suggested that physician's prescription was significant and 88.3% considered pharmacist's guidance in the process of selection of prescription medicines nonessential. A comprehensible and respectable conversation was highly expected in regards to both the OTC and prescription medicines.